2016
DOI: 10.1155/2016/7186140
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of the Bulk-Fill Composite Resins with Different Thickness in Response to Coffee/Water Immersion

Abstract: We aimed to evaluate the color stability of bulk-fill and conventional composite resin with respect to thickness and storage media. Twenty specimens of a conventional composite resin (6 mm diameter and 2 mm thick) and 40 specimens of the bulk-fill Tetric EvoCeram composite resin at two different thicknesses (6 mm diameter and 2 mm thick or 4 mm thick, n = 20) were prepared. The specimens were stored in distilled water during the study period (28 d). Half of the specimens were remained in distilled water and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
0
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(119 citation statements)
references
References 20 publications
6
94
0
19
Order By: Relevance
“…Polishing was shown to partially reduce discoloration, hence suggesting two mechanisms of extrinsic discoloration, pigment absorption within the polymer matrix and pigment adsorption on material surface . Intrinsic discoloration due to hydrolytic changes in the polymer network seem to have a lesser effect on the overall discoloration as color differences after water storage were reported to be smaller compared to colored storage media . Changes in a * and b * showed less consistency in the tested cohort of composites, without a clear shift toward a specific color on the red‐green or blue‐yellow coordinates.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Polishing was shown to partially reduce discoloration, hence suggesting two mechanisms of extrinsic discoloration, pigment absorption within the polymer matrix and pigment adsorption on material surface . Intrinsic discoloration due to hydrolytic changes in the polymer network seem to have a lesser effect on the overall discoloration as color differences after water storage were reported to be smaller compared to colored storage media . Changes in a * and b * showed less consistency in the tested cohort of composites, without a clear shift toward a specific color on the red‐green or blue‐yellow coordinates.…”
Section: Discussionsupporting
confidence: 92%
“…35 Intrinsic discoloration due to hydrolytic changes in the polymer network seem to have a lesser effect on the overall discoloration as color differences after water storage were reported to be smaller compared to colored storage media. 12,14,34,36 Changes in a* and b* showed less consistency in the tested cohort of composites, without a clear shift toward a specific color on the red-green or blue-yellow coordinates. Similar variable findings were reported in previous studies following material exposure to red wine.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies have revealed that these composites can be applied and lightcured in one layer of 4 mm, with low polymerization shrinkage and a high degree of conversion, resulting in less chair time and less gap formation. [16][17][18][19] Polymerization problems are highly diminished according to the higher translucency of the resin materials, which allows for greater light transmission. 16 There are also structural differences between bulk-fill composites and composite resins.…”
Section: Introductionmentioning
confidence: 99%